2017
DOI: 10.3389/fnagi.2017.00048
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Exercise Training for Managing Vascular Risk Factors in Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common form of dementia diagnosed amongst the elderly. Mild cognitive impairment (MCI) is a condition often indicative of the earliest symptomatology of AD with 10%–15% of MCI patients reportedly progressing to a diagnosis of AD. Individuals with a history of vascular risk factors (VRF’s) are considered high risk candidates for developing cognitive impairment in later life. Evidence suggests that vascular injury resulting from untreated VRF’s promotes progression from MCI t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 138 publications
(228 reference statements)
1
10
0
Order By: Relevance
“…Alzheimer’s disease (AD) is the greatest form of dementia, and presently has no effective therapy to improve the symptoms [ 1 , 2 ]. The typical symbol in the diagnosis of AD has been described the increase of neurofibrillary plaques in the brain [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is the greatest form of dementia, and presently has no effective therapy to improve the symptoms [ 1 , 2 ]. The typical symbol in the diagnosis of AD has been described the increase of neurofibrillary plaques in the brain [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this protocol may not increase handgrip strength (Baddeley‐White et al, 2019), there may still be important health benefits. Similar to that observed with aerobic and dynamic resistance exercise, isometric handgrip exercise has been suggested to impact some other health‐related factors including blood pressure (Millar, Paashuis, et al, 2009), pain (Naugle et al, 2012) and cognitive function (Hess & Smart, 2017). In addition, blood lipids (e.g., cholesterol and triglycerides) and lipoproteins (e.g., low‐ or high‐density lipoprotein [HDL or LDL] cholesterol) are well‐studied health‐related factors associated with cardiovascular disease risk (Ference et al, 2020; Mann et al, 2014; Wang & Xu, 2017).…”
Section: Introductionmentioning
confidence: 73%
“…IET can elicit blood pressure (BP) reductions greater than those achieved through aerobic exercise and equivalent to those achieved through monotherapy with beta-blocker [20]. Furthermore, there is a considerable amount of research that links hypertension to conditions of cognitive decline such MCI and AD [21].…”
Section: Ischemic Conditioningmentioning
confidence: 99%
“…Hypertension, a hallmark of aging, has been linked with cerebrovascular pathology, hypoperfusion [22], and cognitive decline [23]. Imaging studies have demonstrated an association between brain atrophy and untreated hypertension [24] and positive correlations have been demonstrated among SBP, diastolic blood pressure, and burden of neural AD pathology [21,25]. Hypertension is associated with structural and functional changes in cerebrovascular pathways.…”
Section: The Role Of Hypertensionmentioning
confidence: 99%